ASSESSMENT OF ANAEROBIC CAPABILITIES OF FOOTBALL PLAYERS IN RELATION WITH LENGTH OF THEIR SPORTS ENGAGEMENT - Milan Cvetković; Slobodan Andrašić; Dejan Orlić; Boris Popović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: The general objective of this research is to determine how much influence the length of sports engagement has on anaerobic endurance of the football players, as well as on the maximum sprint ability of the players. In addition to the primary objective, the research seeks to determine the maximum power, minimum power, average power and fatigue index in players of cadet age group. Methods: The total sample of respondents in this study is made of 60 players of cadet age group (14-16 years of age), divided in relation to length of their sports engagement, into groups of up to 5 years (11 respondents), 6-7 years (21 respondents) and from 8 to 10 years (28 respondents). The study used field RAST test. The RAST test was designed for sports where running is a basic form of movement. According to the protocol of the test respondents have ten minutes to warm up and five minutes to recover. That is followed by the performance of the test, which is composed of six 35-meter sprints at maximum speed. Between sprints respondent is allowed to pause for 10 seconds, intended primarily for turning and preparing for the next section. Based on the obtained time results from six 35-meter sprints, power is calculated for each run and then the following parameters are determined: maximum power (the highest value); minimum power (the lowest value ); average power (the sum of all six values/six) and fatigue index which indicates the extent to which strength decreases for each respondent. This paper shall present a descriptive parameters, mean, standard deviation (SD), minimum and maximum of all values, the coefficient of variation (CV) of confidence intervals, skewness as measure of asymmetry, kurtosis as measure of flatness and value of the Kolmogorov-Smirnov test. Multivariate procedures MANOVA and discriminant analysis shall be used. Out of univariate procedures ANOVA t-test and Roy's test shall be applied. Results: Results obtained by multivariate analysis of variance in this study show that groups are different regarding the observed space of anaerobic abilities of football players. Discriminant analysis confirmed these differences, which means that there is a significant difference and clearly defined boundary between some characteristics for assessing anaerobic abilities in relation to the length of sports engagement. The values obtained by univariate analysis of variance indicate statistically significant differences in all observed variables for the assessment of anaerobic abilities in relation to the length of sports engagement. Discussion: By analyzing the results, it can be concluded that the length of sports engagements and work in this age has positive effects on anaerobic power. Cedric et al. (2007) reached the similar conclusions using the battery of tests for the assessment of anaerobic abilities. On a sample of 186 players of the national team of Belgium (U 15, U 16, U 17, U 18 and U 19) they came to the conclusion that anaerobic power increases progressively with age (15 to 19 yrs.), but the highest increase can be observed between 15th and 17th year of age. References: Cedric L, Marc GV, Thierry B (2007). Journals of Sports Science and Medicine, 10, 115. Cipryan L, Gajda V (2011). Journal of Human Kinetics, 28, 63-71. Mackenzie B (2005). 101 Performance Evaluation Tests. London: Electric Word plc. Sayers A, Sayers B, Binkley H (2008). Strength and Conditioning Journal, 30, 2.